Review of Vojtěch Hladký. Rejoicing Sphairos, Wandering Daimon, and Other Living Beings. Studies on Empedocles’ Philosophy of Life (and Death). Baden-Baden: Karl-Alber Verlag, 2025, 245pp., ISBN 9783495992920 - Casella, Federico (Revista Archai, 2026)
Hladký, Vojtěch. Rejoicing Sphairos, Wandering Daimon, and Other Living Beings. Studies on Empedocles’ Philosophy of Life (and Death). Baden-Baden: Karl-Alber Verlag, 2025. 245pp. 9783495992920